Experimental simulation of rapid clogging process of pervious concrete pavement caused by storm water runoff. Issue Volume 20:Issued 1(2019) (2nd January 2019) - Cui, Xinzhuang; Zhang, Jiong; Huang, Dan; Tang, Weize; Wang, Lei; Hou, Fei
ABSTRACT: Pervious concrete pavements have good drainage capabilities; however, storm water runoff during extreme events can cause the pores clogging in permeable pavement. This study aims to preliminarily reveal the mechanism of sediment clogging in the pores of the pervious concrete pavement under storm water runoff. An innovative continuous permeability measurement system combined with the electrical conductivity measurement is developed. Laboratory simulation tests are conducted with this system to demonstrate the effects of four factors on the permeability reduction. The tests indicate that the pore clogging process generally includes three phases, i.e. quick clogging, temporary mitigation of clogging and progressive clogging. The clogging is more prone to occur in specimens with large porosity. Meanwhile, the variation of electrical conductivity of pervious concrete can accurately reflect the clogging process of pervious concrete. A rapid clogging model has been developed and validated. Research results obtained are important in optimising the design and evaluation of pervious concrete pavement.